A new model for estimating subsurface ice content based on combined electrical and seismic data sets - Hauck, Ch.; Böttcher, M.; Maurer, H. (Copernicus Publications, 2014)
Detailed knowledge of the material properties and internal structures of frozen ground is one of the prerequisites in many permafrost studies. In the absence of direct evidence, such as in-situ borehole measurements, geophysical methods are an increasingly interesting option for obtaining subsurface information on various spatial and temporal scales. The indirect nature of geophysical soundings requires a relation between the measured variables (e.g. electrical resistivity, seismic velocity) and the actual subsurface constituents (rock, water, air, ice). In this work, we present a model which provides estimates of the volumetric fractions of these four constituents from tomographic electrical and seismic images. The model is tested using geophysical data sets from two rock glaciers in the Swiss Alps, where ground truth information in form of borehole data is available. First results confirm the applicability of the so-called 4-phase model, which allows to quantify the contributions of ice-, water- and air within permafrost areas as well as detecting solid bedrock. Apart from a similarly thick active layer with enhanced air content for both rock glaciers, the two case studies revealed a heterogeneous distribution of ice and unfrozen water within Muragl rock glacier, where bedrock was detected at depths of 20–25 m, but a comparatively homogeneous ice body with only minor heterogeneities within Murt`el rock glacier.